2010
DOI: 10.3390/molecules15020959
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Power of the Natural Red Pigment Lycopene

Abstract: By-products derived from food processing are attractive source for their valuable bioactive components and color pigments. These by-products are useful for development as functional foods, nutraceuticals, food ingredients, additives, and also as cosmetic products. Lycopene is a bioactive red colored pigment naturally occurring in plants. Industrial by-products obtained from the plants are the good sources of lycopene. Interest in lycopene is increasing due to increasing evidence proving its preventive properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(152 citation statements)
references
References 175 publications
(204 reference statements)
2
149
0
1
Order By: Relevance
“…It is mainly found in tomatoes but also presented in papaya, guava and watermelon (Shami, Moreira, 2004;Sentanin, Amaya, 2007). It can also be consumed with other active compounds for optimal function in humans (Kong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly found in tomatoes but also presented in papaya, guava and watermelon (Shami, Moreira, 2004;Sentanin, Amaya, 2007). It can also be consumed with other active compounds for optimal function in humans (Kong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene exist in high concentrations in foods like pasta sauce, tomato juice, ketchup, pizza sauce (Tonucci, et al, 1995). It is an acyclic carotenoid and due to its 11 conjugated double bonds it has red color (Kong, et al, 2010). It has no terminal β-ionic ring therefore lycopene has been accepted as non-pro vitamin A precursor so far.…”
Section: Characteristics Of Lycopenementioning
confidence: 99%
“…The results indicated that lycopene supplementation before and after each experimental period were inversely and significantly correlated with those of IGF-1. However, Wang et al have found low evidence for an association between baseline plasma lycopene and the risk of type-2 diabetes in middle-aged and older women after adjustment for multiple risk factors [22].…”
Section: Diabetesmentioning
confidence: 99%
“…On the other hand, lycopene (1-10 μM) was able to inhibit human liver cancerous cells proliferation and preventing them from metastatic process. Lycopene has significantly inversed the proliferation of human colon carcinoma, chronic lymphocytic leukemia, erythroleukemia and Burkitt lymphoma cell lines [22].…”
Section: Cancermentioning
confidence: 99%